2020
DOI: 10.1155/2020/8864412
|View full text |Cite
|
Sign up to set email alerts
|

A Chain Ratio Exponential-Type Compromised Imputation for Mean Estimation: Case Study on Ozone Pollution in Saraburi, Thailand

Abstract: Due to its impact on health and quality of life, Thailand’s ozone pollution has become a major concern among public health investigators. Saraburi Province is one of the areas with high air pollution levels in Thailand as it is an important industrialized area in the country. Unfortunately, the August 2018 Pollution Control Department (PCD) report contained some missing values of the ozone concentrations in Saraburi Province. Missing data can significantly affect the data analysis process. We need to deal with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…The results indicated that the average PM2.5 was 48.20 μg/m 3 with MSE equal to 0.90 μg/m 3 . Chodjuntug and Lawson [19] suggested using a response rate which was free from known parameters and therefore easy to use and also a constant to minimize MSE to estimate the PM2.5 at Kanchana Phisek Road in Bangkok. The Chodjuntug and Lawson estimator [19] was in the form of a regression and exponential estimator under SRSWOR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that the average PM2.5 was 48.20 μg/m 3 with MSE equal to 0.90 μg/m 3 . Chodjuntug and Lawson [19] suggested using a response rate which was free from known parameters and therefore easy to use and also a constant to minimize MSE to estimate the PM2.5 at Kanchana Phisek Road in Bangkok. The Chodjuntug and Lawson estimator [19] was in the form of a regression and exponential estimator under SRSWOR.…”
Section: Introductionmentioning
confidence: 99%
“…Chodjuntug and Lawson [19] suggested using a response rate which was free from known parameters and therefore easy to use and also a constant to minimize MSE to estimate the PM2.5 at Kanchana Phisek Road in Bangkok. The Chodjuntug and Lawson estimator [19] was in the form of a regression and exponential estimator under SRSWOR. The results showed that the mean PM2.5 from their suggested estimator was 42.22 μg/m 3 with MSE of 0.34 μg/m 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation